ANALYSIS OF MODERN WOMEN'S IDDAH AND IHDAD FROM THE FUQAHA PERSPECTIVE - Afadi, Ahmad Alfin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Islam is the complete religion in dealing with humankind from waking up to sleeping, everything has been regulated in Islam, one of which is the obligation of Iddah and Ihdad, both of which are not new laws in this modern era, but both have been around since the time of Rasulullah SAW . The provisions of iddah and ihdad that have been established by Islam are experiencing a bit of a problem in this modern era due to the large number of women who are involved in the world of careers and work to meet the needs of their families therefore the purpose of this research is to examine the opinion of the fuqaha regarding women who undergo iddah and ihdad periods but continues his career outside the home. This study used a qualitative method with the type of library research through a textual approach based on the arguments of the fuqaha scholars who sourced from journals, books, books of scholars and other scientific writings. The author draws the conclusion from this study that women who are in iddah and ihdad are prohibited from marrying before the iddah period is over and are prohibited from leaving the house except for emergencies, and are prohibited from decorating themselves. However, if a woman leaves the house to fulfil her needs, it is permissible in Islamic law, with a note that she does not overdo it when decorating, and it is reasonable.